The Effect Of Injectable Contraception Usage On The Increase In Women's Blood Pressure In The Geneng Community Health Center Area, Ngawi Regency - Dela Alfina; Samuel Budi Harsono L; Santi Dwi Astuti (Fakultas Farmasi Universitas Setia Budi, 2026)
Increased blood pressure in women with hormonal imbalance occurs due to the secretion of angiotensinogen from the liver under endocrine control. This study aimed to determine the blood pressure profile, demographics of contraceptive users, and factors that influence increased blood pressure in the Geneng Community Health Center area, Ngawi Regency. The study design used a retrospective cohort. The sampling technique was purposive sampling adjusted to the inclusion and exclusion criteria. Data analysis was carried out using univariate tests, bivariate tests and multivariate analysis with regression to analyze the effect of injectable contraceptive use on blood pressure. The results of this study indicated that age had the most significant influence on increased blood pressure with 3-month injectable contraceptives using progestin and combination contraceptives with p values ​​of 0.046 <0.05 (3-month progestin contraceptive) and 0.01 <0.05 (3-month combination contraceptive), respectively. The potential for hypertension in the use of 3-month progestin injectable contraceptives was 2,891 times and 3-month combination contraceptive injections was 5,204 times. Other factors such as BMI, number of children, occupation, and education did not significantly influence the incidence of hypertension. There was no significant association between injectable contraceptive use and increased blood pressure with a p-value of 0.365.